2008
DOI: 10.1175/2007mwr2257.1
|View full text |Cite
|
Sign up to set email alerts
|

The Integral Role of a Diabatic Rossby Vortex in a Heavy Snowfall Event

Abstract: On 24-25 February 2005, a significant East Coast cyclone deposited from 4 to nearly 12 in. (ϳ10-30 cm) of snow on parts of the northeastern United States. The heaviest snowfall and most rapid deepening of the cyclone coincided with the favorable positioning of an upper-level, short-wave trough immediately upstream of a preexisting surface cyclone. The surface cyclone in question formed approximately 15 h before the heaviest snowfall along a coastal front in a region of frontogenesis and heavy precipitation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 62 publications
4
24
0
Order By: Relevance
“…First, we confirm the temporal enhancement of the growth rate of the instability due to the condensation that was found by other idealized studies (e.g., Emanuel et al 1987) or case studies (e.g., Wernli et al 2002;Moore et al 2008). Despite this enhancement, we observed that the perturbation energy (diagnosed with different norms) is almost the same after nonlinear saturation of the instability.…”
Section: J O U R N a L O F T H E A T M O S P H E R I C S C I E N C E supporting
confidence: 89%
“…First, we confirm the temporal enhancement of the growth rate of the instability due to the condensation that was found by other idealized studies (e.g., Emanuel et al 1987) or case studies (e.g., Wernli et al 2002;Moore et al 2008). Despite this enhancement, we observed that the perturbation energy (diagnosed with different norms) is almost the same after nonlinear saturation of the instability.…”
Section: J O U R N a L O F T H E A T M O S P H E R I C S C I E N C E supporting
confidence: 89%
“…The NOUL is a simulation without upper-level disturbances. According to Moore et al (2008), upper-level PV anomalies from 500 hPa to the top of the model, which are defined as deviations from the 15-day mean, are excluded from initial and boundary conditions in NOUL using the piecewise PV inversion technique (Davis and Emanuel 1991).…”
Section: Model and Experimental Designmentioning
confidence: 99%
“…Recent studies have indicated that severe convection is excited by a diabatic Rossby vortex (DRV) in a baroclinic zone (Moore et al 2008;Boettcher and Wernli 2011). Parker and Thorpe (1995) presented the first description of the dynamics of DRVs.…”
Section: Introductionmentioning
confidence: 99%
“…Using idealized two-and three-dimensional models, theoretical studies of DRVs by Montgomery (2004, 2005) determined that a low-level, moisture-rich baroclinic field is a key environmental condition for excitation of DRV. Moore and Montgomery (2008) and Boettcher and Wernli (2011) conducted case studies of rapidly intensifying extratropical cyclones, and reported that DRV systems are highly significant in these events.…”
Section: Introductionmentioning
confidence: 99%